Penerapan Metode Demonstrasi dalam Mengembangkan Kemampuan Tahsin Al-Qur’an Siswa - Nuri Iza Muharomah; Moh Sahlan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
A number of vocational school students face obstacles in reading the holy verses of the Koran. The existence of differences in abilities between students requires more intensive guidance with a more effective learning approach. Qualitative descriptive research with data collection carried out through observation and interviews. The results of the research show that the application of the demonstration method in the tahsin program at As-Syafi'i Vocational School in Jember shows positive results in developing students' tahsin abilities through learning makharijul letters, tajwid and tartil carried out interactively, using direct examples from the teacher, from the process the implications show an increase significant in students' understanding of recitation rules and letter pronunciation.